We'll always have the movies : American cinema during World War II - McLaughlin, Robert L., 1957-2022; Parry, Sally E. (Lexington : University Press of Kentucky, 2006)
During the highly charged years of World War II, movies perhaps best communicated to Americans who they were and why they were fighting. These films were more than just an explanation of historical events: they asked audiences to consider the Nazi threat, they put a face on both our enemies and allies, and they explored changing wartime gender roles. We'll Always Have the Movies shows how film after film repeated the narratives, character types, and rhetoric that made the war and each American's role in it comprehensible. Robert L. McLaughlin and Sally E. Parry have watched more than six-hundr.
Before Pearl Harbor -- The war in the Pacific -- Our enemies -- Our fighting allies -- Our occupied allies -- American men and women -- Home-front anxieties -- Postwar films in the postwar world.
Filmography: pages 321-336.
Includes bibliographical references (pages 301-319) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: World War, 1939-1945 -- Motion pictures and the war; World War, 1939-1945 -- United States; Guerre mondiale, 1939-1945 -- Cinéma et guerre; Guerre mondiale, 1939-1945 -- États-Unis.; PERFORMING ARTS -- Film & Video -- Reference; PERFORMING ARTS -- Film & Video -- History & Criticism; War and motion pictures; United States; Film; Krieg; Weltkrieg; USA; Filmkunst; Tweede Wereldoorlog; Verenigde Staten; Andra världskriget och film, USA; Krig och film, USA; 1939-1945